SUBSTITUTION OF SOYBEAN (Glycinemax L. Merril) FLOUR USING KETAPANG (Terminalia catappa) SEED FLOUR ON THE FEED FORMULATION OF TILAPIA (Oreochromis niloticus) - Dewi, Marwa Salnida; Lumbessy, Salnida Yuniarti; Lestari, Dewi Putri (Politeknik Kelautan dan Perikanan Dumai, 2023)
Ketapang (Glycinemax L. Merril) seeds have the potential to become a source of fish feed ingredients derived from vegetables because they are easy to obtain and contain high enough protein. This study attempts to analyze the effect of substitution of soybean flour using ketapang seed flour on the feed formulation of tilapia (Oreochromis niloticus). This study was an experimental study using a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment tested was the concentration of ketapang seed flour, consisting of: A (control/ 0%), B (7%), C (9%), and D (11%). Fish maintenance done for 50 days with an initial size of 4 – 6 g. The observed parameters were absolute weight, absolute length, specific growth rate, feed afficiency, feed convertion ratio, survival rate and water quality. Data were analyzed using analysis of Variance (ANOVA) within 95% of trust. The result showed that substitution of soybean flour using ketapang seed flour on the feed formulation of tilapia (O. niloticus) could affect absolute weight, absolute length, specific growth rate. But did not affect feed afficiency, feed convertion ratio, or survival rate. The addition of 7% ketapang seed formulation gave the best results during the study.